Thermochemical conversion of waste acidic oil into hydrocarbon products over basic composite catalysts. (10th October 2019) - Long, Feng; Li, Fanglin; Zhai, Qiaolong; Wang, Fei; Xu, Junming
Abstract: Removal of oxygen atoms from triglycerides is the most important step in their conversion into hydrocarbons. Basic catalysts have proven to be highly efficient in deoxygenation, whereby the oxygen atoms are removed in the form of CO and CO2, yielding pyrolytic oil with acid number below 10 mg KOH⋅ g −1 . We have now investigated the deoxygenation abilities of composite basic catalysts during the thermochemical conversion process. The dynamics of the catalytic cracking reaction using metal oxides, such as calcium oxide, in the presence of sodium carbonate, has been tested. According to thermogravimetric analysis (TGA) data, the activation energy for catalytic cracking was influenced by cations. By using calcium oxide as a catalyst, the activation energy was reduced from 260 kJ/mol to 185 kJ/mol, leading to a reduction in the reaction temperature of approximately 20–40 °C. The yield of the cracked liquid fraction was of the order of 66–70%, more than 90% of which could be recovered as liquid hydrocarbons. The results presented herein indicate an alternative reaction pathway, allowing thermochemical conversion to be conducted at a lower operational temperature, which would be beneficial for industrial production with lower energy consumption. Graphical abstract: Image 1 Highlights: The basic composite catalyst could remove the oxygen atoms as the form of CO/CO2 . The cleavage product with low acid value. CaO as the catalyst could reduce the cleavage activation. Implying an alternative reaction pathway was beneficial for industrial production with lower energy consumption.